Hubungan antara Dhat dan Sifat Allah Menurut Para Mutakallimun - Ibrahim, Mohd Radhi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2001)
The aim of this articles is to examine the relationship between The God Attributes and His Essence according to Mutakallimun and their polemics on the subject.